Association of necrotizing enterocolitis with antimicrobial exposure in preterm infants <32 weeks gestational age:A multicenter prospective case-control study - Pei, Xiaojing; Gao, Yujun; Kou, Yan; Ding, Yanjie; Li, Dan; Lei, Peng; Zuo, Lili; Liu, Qiongyu; Miao, Naiying; Reddy, Simmy; Yu, Yonghui; Sun, Xuemei (Frontiers in Pharmacology, 2022)
Objective: To assess the risk of necrotizing enterocolitis (NEC) and explore the relationship between antibiotic overexposure and disease occurrence in a large prospective birth cohort. Methods: Based on a prospective birth cohort, the study collected hospitalization data of very preterm infants (VPIs) having gestational age of less than 32 weeks from January 1, 2018, to June 30, 2021 via the China Northern Neonatal Network. Infants diagnosed with NEC ≥ stage II were included in the case group, and each case was matched for GA and birth weight for the control group. Furthermore, the risk factors for NEC were determined by statistical analyses. Results: A total of 6425 VPIs were included in this study, and 167 (2.6%) of these subjects were diagnosed with NEC ≥ stage II. The study also included 984 extremely preterm infants (gestational age <28 weeks), including 50 (5.1%) infants diagnosed with NEC ≥ stage II. In the matched case-control study, subjects had a total of antibiotic days-of-therapy for 9015 days, of which broad-spectrum antibiotics (BSAs) accounted for 77%. The antibiotic spectrum index per antibiotic day in the case group was significantly higher and was an independent risk factor for the occurrence of NEC (p = 0.001, OR = 1.13). Conclusion: The cohort of VPIs was overexposed to antiboitics. Unreasonable combination of antibiotics and overexposure to BSAs may increase the risk of NEC in preterm infants.